AddREssing Social Determinants TO pRevent hypErtension (The RESTORE Network): Overview of the Health Equity Research Network to Prevent Hypertension. (15th April 2023) - Spruill, Tanya M; Muntner, Paul; Popp, Collin J; Shimbo, Daichi; Cooper, Lisa A; Moran, Andrew E; Penko, Joanne; Bibbins-Domingo, Kirsten; Ibe, Chidinma; Nnodim Opara, Ijeoma; Howard, George; Bellows, Brandon K; et al.
Abstract: BACKGROUND: The American Heart Association funded a Health Equity Research Network on the prevention of hypertension, the RESTORE Network, as part of its commitment to achieving health equity in all communities. This article provides an overview of the RESTORE Network. METHODS: The RESTORE Network includes five independent, randomized trials testing approaches to implement non-pharmacological interventions that have been proven to lower blood pressure (BP). The trials are community-based, taking place in churches in rural Alabama, mobile health units in Michigan, barbershops in New York, community health centers in Maryland, and food deserts in Massachusetts. Each trial employs a hybrid effectiveness-implementation research design to test scalable and sustainable strategies that mitigate social determinants of health (SDOH) that contribute to hypertension in Black communities. The primary outcome in each trial is change in systolic BP. The RESTORE Network Coordinating Center has five cores: BP measurement, statistics, intervention, community engagement, and training that support the trials. Standardized protocols, data elements and analysis plans were adopted in each trial to facilitate cross-trial comparisons of the implementation strategies, and application of a standard costing instrument for health economic evaluations, scale up, and policy analysis. Herein, we discuss future RESTORE Network research plans and policy outreach activities designed to advance health equity by preventing hypertension. CONCLUSIONS: The RESTORE Network was designed to promote health equity in the US by testing effective and sustainable implementation strategies focused on addressing SDOH to prevent hypertension among Black adults. Graphical Abstract: